Pengaruh Fintech terhadap Efisiensi Manajemen Keuangan Syariah pada Lembaga Keuangan dan UMKM Syariah di Ponorogo - Masruroh, Binti (Tim Jurnal STAI KH. Zainuddin Ponpes Mojosari, 2025)
This study aims to analyze the impact of the use of Financial Technology (Fintech) on the efficiency of sharia financial management, particularly in sharia financial institutions and sharia-based SMEs in Ponorogo Regency, East Java. The development of fintech provides a significant opportunity to improve the quality and efficiency of financial management in the sharia economic sector, which has long faced challenges in terms of transparency, accountability, and operational efficiency. By leveraging technology, sharia fintech can help SMEs and sharia financial institutions manage their finances in accordance with sharia principles that emphasize justice, transparency, and blessings. This research uses a quantitative approach with a survey technique, involving the distribution of questionnaires to 100 respondents consisting of sharia SMEs, financial managers from sharia financial institutions, and users of sharia fintech services. Respondent selection was carried out using purposive sampling to ensure that the sample involved had an understanding and experience related to the use of fintech in financial management. The collected data was analyzed using simple linear regression to test the relationship between fintech usage and the efficiency of sharia financial management. The results of the study indicate that the use of fintech has a significant impact on improving efficiency in financial management, particularly in aspects such as more systematic financial recording, ease of digital payments, and faster and more accurate financial decision-making. These findings strengthen the importance of digitalizing sharia financial services, particularly in areas like Ponorogo, which has significant potential for sharia-based economic growth. This research is expected to contribute to the development of policies and strategies to improve sharia financial inclusion through the adoption of technology, thereby strengthening the sharia economic ecosystem at both the local and national levels.